Analisis Kuat Lentur Sistem Lantai Curved Tile Semi Pracetak - Mustainul Murtadho; Ismeddiyanto Ismeddiyanto; Enno Yuniarko (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2017)
Semi-precast slab uses the combination of cast-in-place concrete and precast concrete. The use of conventional firmwirk to buid a building was not support for cinstraction method and it’s very expensive for constraction. Some advantages of precast system are related to its time, cost, predictability, reliability, productivity, health, safety, environment, coordination, innovation, reusability also relocability. The research aimed to analyse flexure behaviour of semi precast curved tile concrete slab using finite element software and its comparison to slices method. The analysis model was done in three element of structure, such as support beam, curved tile and cast in place concrete. The model was made in finite element analysis (FEA) program. Simulation done with two location of point load to get pure bending strength of slab. The result analysis has relation to the effect of load towards element bending, flexural moment and crack scheme on model. From the analysis maximum number of load (P) on semi precast slab system with slices method had higher number compared to finite element analysis (Abaqus). Slices method result had maximum number of Pmaks 56.99 kN, while finite element software method had maximum number of Pmaks 47.6 Kn. On semi precast concrete slab, the type of crack that occurred was flexural crack right on the area of highest number of flexural moment an show the crack pattern in the same direction of stirrups on the tensile side of slab.Keywords: slab, support beam, curved tile, semi-precast, cast-in-place, finite element analysis software.